Three-Dimensional Supramolecular Network Directed by Intermolecular Interactions in [Pb2(dmp)2(hfacac)4] - Farzin Marandi; Lotfali Saghatforoush; Hossein Farzaneh (E-Journal of Chemistry)
To investigate the interactions between noncovalent bond donor and acceptor giving rise to three dimensional networks, compound [Pb2(dmp)2(hfacac)2] (1) (dmp = 2,9-dimethyl-1,10-henanthroline and Hhfacac = hexafluoroacetylacetonate) has been prepared and characterized by elemental analysis, IR, 1H NMR, and 13C NMR spectroscopy and its crystal structures was investigated. The single crystal structure show the coordination number of Pb(II) to be eight with two N-donor atoms from a “dmp” ligand and six O-donors from the anionic ligands. The supramolecular structure of 1 is realized by weak directional C–H∙∙∙O–C, C–F∙∙∙F–C and π–π stacking interactions.